Distant organ metastasis patterns and prognosis of cervical adenocarcinoma: a population-based retrospective study - Li, Suyu; Pan, Wuyuan; Song, Jianrong; Zhen, Lan; Chen, Yusha; Liu, Weijian; Zhang, Yulong; Chen, Lingsi; Huang, Qiuyuan; Zheng, Shixiong; Zheng, Xiangqin (Frontiers in Medicine, 2024)
Background: Adenocarcinoma is a common histological subtype of cervical cancer, accounting for 10-15% of all cases. The prognosis of cervical adenocarcinoma with distant organ metastases remains unclear. Therefore, our study aimed to investigate the patterns and prognosis of distant organ metastasis in cervical adenocarcinoma.We obtained data from the Surveillance, Epidemiology, and End Results (SEER) database spanning from 2010 to 2019. Cox regression, Kaplan-Meier, and log-rank analyses were conducted.We observed that adenocarcinoma (AC) of the cervix primarily metastasizes to single organs, with a rate of 73.3%. The lungs are the most common organs of metastasis, followed by the liver and bones. Patients with bone metastases have a median survival period of 12 months, which is slightly longer compared to metastasis in other organs. Distant organ metastasis, age, positive lymph nodes, higher AJCC stages, larger tumor diameter, and higher cell grades are related to poor prognosis (P < 0.001). Furthermore, we have observed that surgical intervention, radiotherapy, and chemotherapy can potentially provide benefits for patients with distant organ metastases.Metastasis is an independent prognostic factor for cervical adenocarcinoma patients. Surgery, radiotherapy, and chemotherapy can provide an overall survival advantage for patients with distant organ metastases.